Monetary poverty and the economic growth cycle of the Huánuco Region, 2009-2018 - Cuadros-Ojeda, Víctor P. (2021)
Objective. Economic growth and monetary poverty are very important economic variables for decision-making in public policy since they allow improving the well-being of the inhabitants of a country, for which the research work established the objective of determining the relationship between these two variables for the department of Huánuco in the period 2009 to 2018. Methods. The research approach was quantitative, applied and descriptive-correlational design. The population and sample consisted of the inhabitants of the Department of Huánuco, whose data were extracted from surveys carried out by the National Institute of Statistics and Informatics (INEI) from 2009 to 2018 and the Central Reserve Bank of Peru. Results. The results showed that there is a negative and average relationship between the variables: Economic growth and monetary poverty (-0.408). Conclusion. It was concluded that the relationship between economic growth and monetary poverty in the department of Huánuco is not significant.